Chinese Encyclopaedias of New Global Knowledge (1870-1930)
X, 472 p. 43 illus.
Keywords: This is a set of pioneering studies on Chinese encyclopaedias of modern knowledge (1870-1930). At a transitional time when modern knowledge was sought after yet few modern schools were available, these works were crucial sources of information for an entire generation. This volume investigates many of these encyclopaedias, which were never reprinted and are hardly known even to specialists, for the first time. The contributors to this collection all specialize in the period in question and have worked together for a number of years. The resulting studies show that these encyclopaedias open a unique window onto the migration and ordering systems of knowledge across cultural and linguistic borders.